ENTRE A FINITUDE E O LIMIAR DA PAIXÃO: "FAZES-ME FALTA", DE INÊS PEDROSA - Santos, Ana Maria Abraão dos (Revista Desassossego, 2009)
This work aims to reflect Inês Pedrosa’s novel, Fazes-me falta (2006), highlighting the relevance of questions about feelings such as friendship and the passion, and also the theme of the death of human beings. In the novel, the death isn’t obstacle to prevent a dialogue in which only two spectral voices cross over the narrative: a woman who died early and an older man, who feels widower, but had never reached a compromise love. That "place without place," "limbo" or "noante," she sees him and she starts a symposium will be composed of fifty textual blocks (half for each). On the threshold between friendship and love, after the separation imposed by her death, both at a distance, they hear it without restrictions and slowing a dialogue in which weave their sufferings and their joys, their affinities and differences, and never expose their feelings had done before. Touches of poetic prose pervaded the dense narrative of writer Portuguese Inês Pedrosa represents issues that are discussed in the (always) complex human relations, its nature and its consequences, before anything definite as death.